Innate and adaptive immune responses of turbot, Scophthalmus maximus (L.), following experimental infection with Enteromyxum scophthalmi (Myxosporea: Myxozoa) - Sitjà-Bobadilla, Ariadna; Redondo, Mª José; Bermúdez, Roberto; Palenzuela, Oswaldo; Ferreiro, Isabel; Riaza, Ana; Quiroga, María Isabel; Nieto, José M.; Álvarez-Pellitero, Mª del Pilar (Fish & Shellfish Immunology, 2006)
The innate and adaptive immune responses against Enteromyxum scophthalmi was studied in turbot (Scopthalmus maximus (L.)) experimentally exposed to the parasite by cohabitation. Haematological, histopathological, cellular and humoral factors were determined in samples taken from control (CTRL) and recipient (RCPT, naïve fish cohabited with donor infected fish) animals at 0, 20, 29, 40 and 43 days post exposure (p.e). Infection was first detected at day 20 p.e. and prevalence reached 100% at 40 days p.e, when first mortalities occurred. A significant reduction in weight and condition factor was found in RCPT, though no significant differences in haematocrit or serum protein levels were detected between CTRL and RCPT. Some immune effectors were clearly activated in RCPT: the percentage of circulating granulocytes was significantly increased, as well as the number of blood cells positive in the respiratory burst assay; leucocyte infiltration in intestine was found mainly on days 20 and 29 p.e.; total serum antiproteases and α-2-macroglobulin levels were higher in most of the samplings, with significant differences on the last sampling. Other effectors were clearly down regulated in RCPT: haematopoietic depletion appeared in head kidney from day 29 p.e. onwards, and the number of apoptotic cells and MMC increased in head kidney and spleen; the percentage of lymphocytes decreased progressively and significantly; a clear, but not statistically significant, drop in serum complement was registered at 40 days p.e.; also, a significant decrease occurred in serum lysozyme at 29 days p.e. No specific antibodies against the parasite were detected in any sampling. Funding for this work was obtained from the Spanish Ministry of Science and Technology through research project AGL-2001-2241-C01, from Xunta de Galicia through the project PGIDIT 02RMA25E, and from Stolt Sea Farm, S.A. through a research contract. R. Bermúdez was recipient of a predoctoral fellowship from the Spanish Ministry of Education and Science. We are ...